Coping strategies used by patients with relapsing multiple sclerosis from Argentina: correlation with quality of life and clinical features. (1st February 2021) - Carnero Contentti, Edgar; López, Pablo A.; Alonso, Ricardo; Eizaguirre, Barbara; Pettinicchi, Juan Pablo; Tizio, Santiago; Tkachuk, Verónica; Caride, Alejandro
ABSTRACT: Background: Multiple sclerosis (MS) is a chronic neurodegenerative and inflammatory disease. The adaptation to MS depends on the effectiveness of coping, which moderates the process of adaptation and psychological well-being. Objectives: We aimed to analyze the coping strategies of an Argentinean population of patients with MS (PwMS) and their association with clinical variables and health-related quality of life (QoL). Methods: A nationwide cross-sectional study. Screening instruments: Demographics and clinical data, coping strategies (Brief Coping Orientation to Problems Experienced, [COPE-28]), health-related QoL (MS Impact Scale, [MSIS-29]), Fatigue Severity Scale, and physical disability (self-administrated Expanded Disability Status Scale, [EDSS]). Results: We included 249 PwMS. Most responders were female (74.7%) with a mean age at survey of 38.6 (±10.7) and had a MS duration of 7.3 years (range: 1–43 years) and a mean EDSS of 1.9 (±1.8). Younger age (r = −0.17), active MS (r = 0.25), higher fatigue (r = 0.22), MSIS-29 total (r = 0.34), MSIS-physical (r = 0.26), MSIS-psychological scores (r = 0.44), higher scores for perception of both severity of MS (r = 0.12) and wheelchair-dependency (r = 0.14) correlated significantly with the use of maladaptive coping strategies. However, active MS (β2.10, p = 0.01), MSIS-psychological score (β0.28, p < 0.0001), high education level (β − 1.15, p = 0.04), and EDSS (β − 0.84, p = 0.0001) were independent predictors of the utilization of maladaptive coping strategies after having applied multivariate analysis via linear regression. Conclusions: Maladaptive coping strategies used by PwMS are associated with relevant clinical aspects of the disease and with worse health-related QoL scores.